Pediatric Cardiac Transplantation Using Hearts Previously Refused for Quality: A Single Center Experience. Issue 6 (6th May 2013) - Easterwood, R.; Singh, R. K.; McFeely, E. D.; Zuckerman, W. A.; Addonizio, L. J.; Gilmore, L.; Beddows, K.; Chen, J. M.; Richmond, M. E.
Abstract Pediatric donor hearts are regularly refused for donor quality with limited evidence as to which donor parameters are predictive of poor outcomes. We compare outcomes of recipients receiving hearts previously refused by other institutions for quality with the outcomes of recipients of primarily offered hearts. Data for recipients aged ≤18 and their donors were obtained. Specific UNOS refusal codes were used to place recipients into refusal and nonrefusal groups; demographics, morbidity and mortality were compared. Kaplan–Meier analysis with log‐rank test was used to determine differences in graft survival. A multivariable Cox proportional hazards model was constructed to determine independent risk factors for postoperative mortality. From July 1, 2000 to April 30, 2011, 182 recipients were transplanted and included for analysis. One hundred thirty received a primarily offered heart; 52 received a refused heart. No difference in postoperative complications or graft survival between the two groups (p = 0.190) was found. Prior refusal was not an independent risk factor for recipient mortality. Analysis of this large pediatric cohort examining outcomes with quality‐refused hearts shows that in‐hospital morbidity and long‐term mortality for recipients of quality‐refused hearts are no different than recipients of primarily offered hearts, suggesting that donor hearts previously refused for quality are not necessarily unsuitable for transplant and often show excellent outcomes.